3D simulation study on the influence of lubricant oil droplets on pre-ignition in turbocharged DISI engines. (October 2018) - Huang, Yongcheng; Li, Yaoting; Zhang, Wenjia; Meng, Fansheng; Guo, Zhechen
A skeletal chemical kinetic model for the simulation of auto-ignition and flame propagation characteristics of primary reference fuel (PRF) was developed. Coupled with this model, 3D simulations were applied to investigate the influence of lubricant oil droplets on pre-ignition in a turbocharged direct-injection spark-ignition (DISI) engine at low-speed high-load operating conditions. First, a simulation study on the influence of a lubricant oil droplet on auto-ignition of gasoline substitute and air mixture was performed in a constant-volume chamber. The results revealed that with an increase of the lubricant oil droplet diameter, the ignition delay time for the air/fuel mixture initially decreased and then increased. The ignition delay time was further shortened with the increase of the temperature of the lubricant oil droplet and the temperature and pressure of the mixture. Moreover, it was found that when n-heptane (n-C7 H16 ) was used as a substitute for the direct evaporation product of the lubricant oil droplet, the shortening of the ignition delay time for the air/fuel mixture caused by lubricant oil evaporation was not enough to initiate pre-ignition. When octyl hydrogen peroxide ketone (C8 KET) was chosen as a representative of the accumulated stable reactive radicals, the ignition delay time was significantly shortened and was short enough to trigger pre-ignition. Therefore, pre-ignition may not be induced by the direct evaporation product of an lubricant oil droplet but by the accumulated stable reactive radicals. A simulation study on auto-ignition and flame propagation of the air/fuel mixture with the presence of a lubricant oil droplet was then conducted in a turbocharged DISI engine. The results successfully predicted the auto-ignition of the air/fuel mixture near the lubricant oil droplet before the spark ignition timing. Finally, a more convincing mechanism for pre-ignition induced by lubricant oil droplets is proposed to provide some clues for further investigation.